ON THE THOMAS-FERMI EQUATION - Hille, Einar (1969)
A study has been made of some mathematical aspects of the Thomas-Fermi equation. This is a preliminary report on the results obtained, including (1) convergence of relevant series, (2) existence of unbounded solutions, (3) existence of solutions having an arbitrary branch point, (4) determination of a class of solutions bounded for large values of the variable, and (5) determination of a class of solutions unbounded for small values.